UNITÉ DE DOCTRINE – CONTINGENCY OF PRACTICE? TOWARDS A RE-READING OF TWENTIETH CENTURY PRINCIPLES OF BUILDING HERITAGE CONSERVATION - Andreas Putz (Ochrona Dziedzictwa Kulturowego, 2019)
The theoretical framework of building heritage conservation is not necessarily a predefined set of tenets and axioms with potentially universal significance, but a result of particular challenges and practices bound in time and place. In this article, the guidelines of building heritage conservation in Switzerland in the last century are outlined briefly with reference to the broader European theoretical discourse. Focusing on the contradictions between the theoretical position and practical work of Linus Birchler, it argues for the necessity to re-read and assess our principles of building heritage conservation in relation to the specific built cases they originated from.